THE IMPACT OF OPERATING COST AND REVENUE BUDGETING ON FINANCIAL PERFORMANCE: EVIDENCE FROM BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2021–2024) - Hasibuan, Renika; Simanullang, Refika Sriwidawati; Zega, Yefta; Ningsih , Thresia Ita Sri; Laia , Arianti; Sirait , Yesica Tina Claudia (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2026)
This study aims to examine both partially and simultaneously the effect of operating cost budgets and revenue budgets on the financial performance of financial service companies in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The population of this study consists of 47 banking companies listed on the Indonesia Stock Exchange. A quantitative research method was employed, using purposive sampling to select 11 companies, resulting in a total of 44 observations. Data were collected from annual reports and audited financial statements published by banking sector financial service companies listed on the Indonesia Stock Exchange. The data analysis technique used was multiple linear regression, processed using IBM SPSS version 30. The results indicate that the operating cost budget plan has no partial effect on financial performance, while the revenue budget plan has a partial effect on financial performance. However, the operating cost budget plan and the revenue budget plan simultaneously have a significant effect on the financial performance of financial service companies in the banking sector listed on the Indonesia Stock Exchange.